Expression patterns of HLA-DR+ or HLA-DR- on CD4+/CD25++/CD127low regulatory T cells in patients with allergy - Geraldes, L (2010)
BACKGROUND: Allergic rhinoconjunctivitis induced by pollen is a highly prevalent chronic inflammatory disease in Europe. Parietariajudaica is a frequent trigger in the Mediterranean area. The function of regulatory T cells (Treg cells) in allergy has recently been investigated, but further data are necessary to better understand their role and to find new strategies to treat allergic diseases such as allergic rhinoconjunctivitis. OBJECTIVE: To characterize gene expression of HLA-DR+ or HLA-DR- on peripheral CD4+/CD25++/CD127low Treg cells in patients with allergy. METHODS: Peripheral Treg cells (CD4+/CD25++/CD127low) were quantified using flow cytometry and sorted according to HLA-DR expression during the pollen season in patients with allergic rhinoconjunctivitis caused by P. judaica. The results were compared with those of nonatopic controls. Expression of associated cytokines and their receptors was measured using quantitative reverse transcription-polymerase chain reaction after extraction of mRNA in sorted populations. RESULTS: During the pollen season, no significant differences were observed between allergic patients with rhinoconjunctivitis and healthy controls in terms of the absolute number or the percentage of Treg cells in peripheral blood. All patients had a higher number/percentage of HLA-DR- Treg cells than HLA-DR+ Treg cells. In both groups we found high levels of FOXP3 mRNA expression. Despite being lower in number, HLA-DR+ Treg cells presented higher expression of CD28, PRF1, GZMB, and FASL than HLA-DR-Treg cells. CONCLUSIONS: The most relevant results obtained suggest that HLA-DR+ Treg cells tend to present higher gene expression of molecules associated with contact-dependent cell activation and cytotoxicity.